Z-Transform: e N X e X
Z-Transform: e N X e X
Fourier Transform
( ) = ∑ x[n]e
∞
jw − jwn
X e
n = −∞
z-transform
∞
X (z ) = ∑ x[n]z −n
n = −∞
Z-Transform (continue)
Z-transform operator: Z{⋅ }
∞
Z {x[n]} = ∑ x[k ]z − k = X (z )
k = −∞
The z-transform operator is seen to transform the
sequence x[n] into the function X{z}, where z is a
continuous complex variable.
From time domain (or space domain, n-domain) to the
z-domain
∞
x[n] = ∑ x[k ]δ [n − k ] ↔ Z {x[n]} = X (Z )
z
k = −∞
Bilateral vs. Unilateral
Two sided or bilateral z-transform
∞
X (z ) = ∑ x[n]z − n
n = −∞
Unilateral z-transform
∞
X (z ) = ∑ x[n]z −n
n =0
Example of z-transform
n n≤−1 0 1 2 3 4 5 N>5
x[n] 0 2 4 6 4 2 1 0
X (z ) = 2 + 4 z −1
+ 6z −2
+ 4z −3
+ 2z −4
+z −5
Relationship to the Fourier
Transform
If we replace the complex variable z in the z-
transform by ejw, then the z-transform reduces to
the Fourier transform.
The Fourier transform is simply the z-transform
when evaluating X(z) in a unit circle in the z-plane.
Generally, we can express the complex variable z in the
polar form as z = rejw. With z expressed in this form,
( ) ∑ x[n](re ) ∑ (x[n]r )e
∞ ∞
jw − n −n − jwn
X re jw = =
n = −∞ n = −∞
Relationship to the Fourier
Transform (continue)
In this sense, the z-transform can be interpreted as
the Fourier transform of the product of the original
sequence x[n] and the exponential sequence r−n.
For r=1, the z-transform reduces to the Fourier transform.
m =0
x[n] y[n]
h[n]
X(z) Y(z)
H(z)
Multiplication Rule of
Cascading System
X(z) Y(z)
≡ H1(z)H2(z)
Example
Consider the FIR system y[n] = 6x[n] − 5x[n−1] + x[n−2]
The z-transform system function is
H (z ) = 6 − 5 z −1
+z −2
⎛ 1 ⎞⎛ 1⎞
⎜ z − ⎟⎜ z − ⎟
(
= 3− z −1
)(2 − z )
−1
=6 ⎝ 3 ⎠⎝
z 2
2⎠
Delay of one Sample
Consider the FIR system y[n] = x[n−1], i.e., the one-
sample-delay system.
The z-transform system function is
H (z ) = z −1
z −1
Delay of k Samples
Similarly, the FIR system y[n] = x[n−k], i.e., the k-
sample-delay system, is the z-transform of the
impulse response δ[n − k].
H (z ) = z −k
z −k
System Diagram of A Causal
FIR System
The signal-flow graph of a causal FIR system
can be re-represented by z-transforms.
x[n] b0 + x[n] b0 +
y[n] y[n]
TD z− 1
x[n-1] b1 + x[n-1] b1 +
TD z−1
x[n-2] b2 + x[n-2] b2 +
TD z−1
x[n-M] bM + x[n-M] bM +
Z-transform of General
Difference Equation
Remember that the general form of a linear
constant-coefficient difference equation is
N M
∑ ak y[n − k ] = ∑ bm x[n − m] for all n
k =0 m =0
x[n] b0 + + y[n]
TD TD
x[n-1] b1 + + − a1 y[n-1]
TD TD
x[n-2] b2 + + − a2 y[n-2]
TD
TD
+ − aN y[n-N]
x[n-M] bM +
Z-transform of Linear Constant-
coefficient Difference Equation
The signal-flow graph of difference
equations represented by z-transforms.
X(z) b0 + + Y(z)
z−1 z−1
b1 + + − a1
z−1 z−1
b2 + + − a2
z−1
z−1
+ − aN
bM +
Z-transform of Difference
Equation (continue)
From the signal-flow graph,
M N
Y (z ) = ∑ bm X (z )z − m − ∑ a k Y (z )z − k
m =0 k =1
N M
Thus, ∑ k
a Y ( z )z −k
= ∑m
b X ( z )z −m
k =0 m =0
M
∑
Y (z ) m = 0
bm z − m
We have =
X (z )
N
∑ ak z − k
k =0
Z-transform of Difference
Equation (continue)
M N
Let H [z ] = ∑ bm z − m / ∑ ak z −k
m =0 k =0
H(z) is called the system function of the LTI system defined
by the linear constant-coefficient difference equation.
The multiplication rule still holds: Y(z) = H(z)X(z), i.e.,
Z{y[n]} = H(z)Z{x[n]}.
The system function of a difference equation is a rational
form X(z) = P(z)/Q(z).
Since LTI systems are often realized by difference equations,
the rational form is the most common and useful for z-
transforms.
Z-transform of Difference
Equation (continue)
When ak = 0 for k = 1 … N, the difference equation
degenerates to a FIR system we have investigated
before. M
H (z ) = ∑bm z − m
m =0
H (z ) = m =0
zM
System Function and Impulse
Response
When the input x[n] = δ[n], the z-transform of
the impulse response satisfies the following
equation:
Z{h[n]} = H(z)Z{δ[n]}.
Since the z-transform of the unit impulse δ[n] is
equal to one, we have
Z{h[n]} = H(z)
That is, the system function H(z) is the z-
transform of the impulse response h[n].
System Function and Impulse
Response (continue)
Generally, for a linear system,
y[n] = T{x[n]}
it can be shown that
Y{z} = H(z)X(z).
where H(z), the system function, is the z-transform of the
impulse response of this system T{⋅}.
Also, cascading of systems becomes multiplication of
system function under z-transforms.
The zeros of this system are 1/3 and 1/2, and the
pole is 0.
Since 0 and 0 are double roots of Q(z), the pole
is a second-order pole.
Example: Right-sided
Exponential Sequence
Right-sided sequence:
A discrete-time signal is right-sided if it is nonzero
only for n≥0.
Consider the signal x[n] = anu[n].
∑ (az )
∞ ∞
X (z ) = ∑ a u[n]z
n −n
= −1 n
∑ (az )
∞
X (z ) = −1 n 1 z
= −1
= , z > a
n =0 1 − az z−a
There is one zero, at z=0, and one pole, at z=a.
: zeros
× : poles
Gray region: ROC
Example: Left-sided Exponential
Sequence
Left-sided sequence:
A discrete-time signal is left-sided if it is nonzero only
for n ≤ −1.
Consider the signal x[n] = −anu[−n−1].
∞ −1
X (z ) = − ∑ a n u[− n − 1]z − n = − ∑ a n z −n
n = −∞ n = −∞
∑ (a z )
∞ ∞
∑a −n n −1 n
= z = 1−
n =1 n =0
⎛ 1⎞
2 z⎜ z − ⎟
=
1
+
1
= ⎝ 12 ⎠
1 −1
1− z
1 −1
1+ z ⎛ 1 ⎞⎛ 1⎞
⎜ z − ⎟⎜ z + ⎟
2 3 ⎝ 2 ⎠⎝ 3⎠
Example: Sum of Two
Exponential Sequences (continue)
n
⎛1⎞ z
⎜ ⎟ u (n )
1 1
⎝2⎠
↔ 1 −1
, z >
2
1− z
n 2
⎛ 1⎞ z
⎜ − ⎟ u (n )
1 1
⎝ 3⎠
↔ 1 −1
, z >
3
1+ z
Thus 3
n n
⎛1⎞ ⎛ 1⎞ z
⎜ ⎟ u (n ) + ⎜ − ⎟ u (n )
1 1 1
⎝2⎠ ⎝ 3⎠
↔ 1 −1
+
1 −1
, z >
2
1− z 1+ z
2 3
Example: Sum of Two
Exponential Sequences (continue)
Example: Two-sided Exponential
Sequence
n n
⎛ 1⎞ ⎛1⎞
Given x(n ) = ⎜ − ⎟ u (n ) − ⎜ ⎟ u (− n − 1)
⎝ 3⎠ ⎝2⎠
n
⎛ 1⎞ z
⎜ − ⎟ u (n )
1 1
Since
⎝ 3⎠
↔ 1 −1
, z >
3
1+ z
3
and by the left-sided sequence example
n
⎛1⎞ z
− ⎜ ⎟ u (− n − 1)
1 1
⎝2⎠
↔ 1 −1
, z <
2
1− z
2
Example: Two-sided Exponential
Sequence (continue)
⎛ 1⎞
2 z⎜ z − ⎟
X (z ) =
1
+
1
= ⎝ 12 ⎠
1 −1
1+ z
1 −1
1− z ⎛ 1 ⎞⎛ 1⎞
⎜ z + ⎟⎜ z − ⎟
3 2 ⎝ 3 ⎠⎝ 2⎠
−1
n =0 n =0 1 − az
1 z −a
N N
= N −1
z z−a
There are the N roots of zN = aN, zk = aej(2πk/N). The root of k = 0
cancels the pole at z=a. Thus there are N−1 zeros, zk =
aej(2πk/N), k = 1 …N, and a (N−1)th order pole at zero.
Pole-zero Plot
Some Common Z-transform
Pairs
δ [n] ↔ 1 ROC : all z.
u[n] ↔
1
−1
ROC : z > 1.
1− z
− u[− n − 1] ↔
1
−1
ROC : z < 1.
1− z
δ [n − m] ↔ z − m ROC : all z except 0 (if m > 0) or ∞ (if m < 0) .
a n u[n] ↔
1
−1
ROC : z > a .
1 − az
− a n u[n] ↔
1
ROC : z < a .
1 − az −1
az −1
na u[n] ↔
n
ROC : z > a .
(1 − az ) −1 2
Some Common Z-transform
Pairs (continue)
az −1
− na u[− n − 1] ↔
n
ROC : z < a .
(1 − az )
−1 2
1 − [cos w0 ]z −1
[cos w0 n]u[n] ↔ ROC : z > 1.
1 − [2 cos w0 ]z −1
+z −2
[r sin w0 ]z −1
[r sin w0 n]u[n] ↔ 1 − [2r cos w ]z −1 + r 2 z −2
n
ROC : z > r.
0
⎧⎪a n 0 ≤ n ≤ N −1 1− a N z −N
⎨ ↔ −1
ROC : z > 0.
⎪⎩ 0 otherwise 1 − az
Properties of the ROC
The ROC is a ring or disk in the z-plane centered at
the origin; i.e., 0 ≤ rR < |z| ≤ rL ≤ ∞.
The Fourier transform of x[n] converges absolutely
iff the ROC includes the unit circle.
The ROC cannot contain any poles
If x[n] is a finite duration sequence, then the ROC is
the entire z-plane except possible z=0 or z=∞.
If x[n] is a right-sided sequence, the ROC extends
outward from the outermost (i.e., largest magnitude)
finite pole in X(z) to (and possibly include) z=∞.
Properties of the ROC
(continue)
If x[n] is a left-sided sequence, the ROC extends
inward from the innermost (i.e., smallest
magnitude) nonzero pole in X(z) to (and possibly
include) z = 0.
A two-sided sequence x[n] is an infinite-duration
sequence that is neither right nor left sided. The
ROC will consist of a ring in the z-plane, bounded
on the interior and exterior by a pole, but not
containing any poles.
The ROC must be a connected region.
Properties of the ROC
(continue)
Consider the system function H(z) of a linear
system:
If the system is stable, the impulse response h(n) is
absolutely summable and therefore has a Fourier
transform, then the ROC must include the unit circle,.
If the system is causal, then the impulse response h(n)
is right-sided, and thus the ROC extends outward from
the outermost (i.e., largest magnitude) finite pole in H(z)
to (and possibly include) z=∞.
Inverse Z-transform
Given X(z), find the sequence x[n] that has X(z) as
its z-transform.
We need to specify both algebraic expression and
ROC to make the inverse Z-transform unique.
Techniques for finding the inverse z-transform:
Investigation method:
By inspect certain transform pairs.
Eg. If we need to find the inverse z-transform of
X (z ) =
1
1 − 0.5 z −1
From the transform pair we see that x[n] = 0.5nu[n].
Inverse Z-transform by
Partial Fraction Expansion
M
If X(z) is the rational form with
∑ bm z − m
X (z ) = m =0
N
∑ ak z − k
k =0
An equivalent expression is
M M
z −M ∑ bm z M − m zN ∑ bm z M − m
X (z ) = m =0
N
= m =0
N
z −N ∑ ak z N − k z M
∑ ak z N − k
k =0 k =0
Inverse Z-transform by Partial
Fraction Expansion (continue)
There will be M zeros and N poles at nonzero
locations in the z-plane.
Note that X(z) could be expressed in the form
∏ (1 − c )
M
−1
m z
X (z ) =
b0 m =1
∏ (1 − d z )
a0 N
−1
k
m =1
where ck’s and dk’s are the nonzero zeros and
poles, respectively.
Inverse Z-transform by Partial
Fraction Expansion (continue)
Then X(z) can be expressed as
N
X (z ) = ∑
Ak
−1
k =1 1 − d k z
Obviously, the common denominators of the
fractions in the above two equations are the same.
Multiplying both sides of the above equation by
1−dkz−1 and evaluating for z = dk shows that
(
Ak = 1 − d k z −1
)X (z ) z =dk
Example
Find the inverse z-transform of
X (z ) =
1 1
z >
( )(
1 − (1 / 4)z −1 1 − (1 / 2 )z −1 ) 2
X(z) can be decomposed as
X (z ) =
A1 A2
+
(
1 − (1 / 4 )z −1
) (
1 − (1 / 2 )z −1 )
Then
( )
A1 = 1 − (1 / 4 )z −1 X (z ) z =1 / 4 = −1
A2 = (1 − (1 / 2 )z )X (z )
−1
z =1 / 2 =2
Example (continue)
Thus
−1
X (z ) =
2
+
(1 − (1 / 4)z ) (1 − (1 / 2)z )
−1 −1
and so
n n
⎛1⎞ ⎛1⎞
x[n] = 2⎜ ⎟ u[n] − ⎜ ⎟ u[n]
⎝2⎠ ⎝4⎠
Another Example
Find the inverse z-transform of
X (z ) =
(1+ z )
−1 2
z >1
(1 − (1 / 2)z )(1 − z )
−1 −1
X (z ) = B0 +
A1 A2
+
(1 − (1 / 2)z ) (1 − z )
−1 −1
(1 − (1 / 2 )z )
−1
− 1 + 5z −1
A = 2+ =9
1
(1 − (1 / 2)z )(1 − z )
−1 −1 z =1 / 2
(
1− z )
−1
− 1 + 5z −1
A = 2+ =8
2
(1 − (1 / 2)z )(1 − z )
−1 −1 z =1
X (z ) = 2 −
Therefore 9 8
+
(1 − (1 / 2)z ) (1 − z )
−1 −1
X (z ) = z − 0.5 z − 1 + 0.5 z
2 −1
Thus,
x[n] = δ [n + 2] − 0.5δ [n + 1] − δ [n] + 0.5δ [n − 1]
Example
Find the inverse z-transform of
(
X (z ) = log 1 + az −1
) z > a
Using the power series expansion for log(1+x) with
|x|<1, we obtain
X (z ) =
∞
(− 1) a n z − n
n +1
∑ n
n =1
⎧⎪(− 1)n +1 a n / n n ≥ 1
Thus x[n] = ⎨
⎪⎩ 0 n≤0
Z-transform Properties
Suppose x[n] ↔ X (z )
z
ROC = R x
x1 [n] ↔ X 1 (z )
z
ROC = R x1
x2 [n] ↔ X 2 (z )
z
ROC = R x2
Linearity
x[n − n0 ] ↔ z − n0 X (z )
z
ROC = R x (except for the
possible addition
or deletion of z=0
or z=∞.)
Multiplication by an exponential sequence
z 0n x[n] ↔ X (z / z 0 )
z
ROC = z 0 R x
Z-transform Properties
(continue)
Differentiation of X(z)
dX (z )
nx[n] ↔
z
−z ROC = R x
dz
Conjugation of a complex sequence
x * [n] ↔ X * (z * )
z
ROC = R x
Z-transform Properties
(continue)
Time reversal
x * [− n] ↔ X * (1 / z * )
z 1
ROC =
Rx
If the sequence is real, the result becomes
x[− n] ↔ X (1 / z )
z 1
ROC =
Rx
Convolution
x1 [n]∗ x2 [n] ↔ X 1 (z )X 2 (z )
z
ROC contains R x1 ∩ R x2
Z-transform Properties
(continue)
Initial-value theorem: If x[n] is zero for n<0 (i.e., if
x[n] is causal), then
x[0] = lim X (z )
z →∞